2012
DOI: 10.1186/ar4094
|View full text |Cite
|
Sign up to set email alerts
|

Reverse regulation of soluble receptor for advanced glycation end products and proinflammatory factor resistin and S100A12 in Kawasaki disease

Abstract: IntroductionKawasaki disease (KD), an acute febrile disease, characterized by systemic vasculitis, predominantly affects infants and children under 5 years of age. Coronary artery lesions (CALs) are its most critical complication, and the etiology remains unknown yet. In order to explore the value of resistin, S100A12 and soluble receptor for advanced glycation end products (sRAGE) in the pathophysiology of KD, we studied the serum levels of resistin, S100A12 and sRAGE in different stages of KD.MethodsSerum le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…By detecting the expression of HMGB1, sRAGE, and NF-κB in serum, we found that the levels of the three indicators were increased in the S group. Although there are reports that sRAGE is reduced in the acute phase of KD [31], we tested the serum of patients with KD and in a young rabbit model of KD, and found that it was increased in the acute phase, which may be related to the number of cases or time or regional disparity. In addition, some studies have reported that sRAGE is elevated in the acute phase of some diseases; for example, in patients with infectionrelated ARDS, sRAGE levels have been shown to be much higher than those in the control subjects [32].…”
Section: Discussionmentioning
confidence: 87%
“…By detecting the expression of HMGB1, sRAGE, and NF-κB in serum, we found that the levels of the three indicators were increased in the S group. Although there are reports that sRAGE is reduced in the acute phase of KD [31], we tested the serum of patients with KD and in a young rabbit model of KD, and found that it was increased in the acute phase, which may be related to the number of cases or time or regional disparity. In addition, some studies have reported that sRAGE is elevated in the acute phase of some diseases; for example, in patients with infectionrelated ARDS, sRAGE levels have been shown to be much higher than those in the control subjects [32].…”
Section: Discussionmentioning
confidence: 87%
“…In 50 children with acute Kawasaki disease, sRAGE levels were decreased in patients with high disease activity and in non-responders after intravenous immunoglobulin treatment, being inversely correlated to S100A12 [ 190 ]. These findings were lately backed by Qi et al , who found sRAGE levels to be significantly lower in the acute stage of Kawasaki disease and increased in afebrile and subacute stages, again being negatively correlated with S100A12 and resistin [ 191 ].…”
Section: Clinical Relevance Of Circulating Hmgb1 and Sragementioning
confidence: 92%
“…RAGE was first isolated and characterized in 1992 from the endothelial surface [21]. This multiligand cell-surface receptor has been shown to be expressed on several other cell lines, including smooth muscle cells, mononuclear phagocytes, T-lymphocytes, cardiac myocytes, and [32] Plasma esRAGE levels were inversely correlated with IMT in nondiabetic patients with atherosclerosis Qi et al, 2012 [33] Falcone et al, 2005 [16] Coronary artery disease Inverse association between plasma sRAGE levels and CAD neurons [22,23]. The full-length RAGE (flRAGE) is made up of three separate domains: an extracellular multiple receptor-containing domain, a transmembrane domain, and an intracellular cytoplasmic tail [24].…”
Section: The Biology Of Rage-ligand Axismentioning
confidence: 99%
“…The first study to report total serum sRAGE level in relation to disease presence demonstrated that patients with the lowest levels of sRAGE presented with a higher risk for CAD-a dose-dependent inverse relationship [14]. Additionally, other vascular disorders have been examined for sRAGE levels and are summarized in Table 1 [32][33][34][35][36][37][38]. Such research has led to possible establishment of a biomarker for non-ST segment myocardial infarction (NSTEMI) [15].…”
Section: The Soluble Receptor For Advanced Glycated End-productsmentioning
confidence: 99%